Information Seeking Anxiety and Preferred Information Sources of First-Generation College Students - Brinkman, Stacy; Smith, Josefine (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – To determine whether information seeking anxieties and preferred information sources differ between first-generation college students and their continuing-generation peers. Methods – An online survey was disseminated at two public college campuses. A total of 490 respondents were included in the results. Independent variables included institution, year in college, and generational status. Instead of using a binary variable, this study used three groups for the independent variable of generational status, with two first-generation groups and one continuing-generation group based on parental experience with college. Dependent variables included 4 measures of information seeking anxiety and 22 measures of preferred information sources. Responses were analyzed using SPSS. One-way independent ANOVA tests were used to compare groups by generational status, and two- and three-way factorial ANOVA tests were conducted to explore interaction effects of generational status with institution and year in college. Results – No significant differences in overall information seeking anxiety were found between students whose parents had differing levels of experience with college. However, when exploring the specific variable of experiencing anxiety about “navigating the system in college,” a two-way interaction involving generational status and year in school was found, with first-generation students with the least direct experience with college reporting higher levels of anxiety at different years in college than their peers. Two categories of first-generation students were found to consult with their parents far less than continuing-generation peers. The study also found that institutional or generational differences may also influence whether students ask for information from their peers, librarians, tutoring centers, professors, or advisors. Conclusion – This study is one of the first to directly compare the information seeking preferences and anxieties of first-generation and continuing-generation students using a non-binary approach. While previous research suggests that first-generation students experience heightened anxiety about information seeking, this study found no significant overall differences between students based on their generational status. The study reinforced previous research about first-generation college students relying less on their parents than their continuing-generation peers. However, this study complicates previous research about first-generation students and their utilization of peers, librarians, tutoring centers, professors, or advisors as information sources, and suggests that institutional context plays an important role in shaping first-generation information seeking.